2020
DOI: 10.1111/jphp.13185
|View full text |Cite
|
Sign up to set email alerts
|

Chemical constituents, experimental and clinical pharmacology of Rosa damascena: a literature review

Abstract: Context Rosa damascena Mill. is prescribed for the management of chest and abdominal pain, constipation, digestive disorders, menstrual bleeding and liver ailments. Objective The current review compiles up to date and complete information of whole plant of R. damascena with particular emphasis on its numerous scientifically proved pharmacological effects, traditional and folk medicinal uses. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(68 citation statements)
references
References 52 publications
2
66
0
Order By: Relevance
“…It is a considerable remedy in traditional medicine and a cost-effective herbal therapy with curative utilization in modern medicine (27). In Persian medicine, Rosa damascene is considered a gentle safe laxative and even can be prescribed for children and pregnant women (19,28).…”
Section: Discussionmentioning
confidence: 99%
“…It is a considerable remedy in traditional medicine and a cost-effective herbal therapy with curative utilization in modern medicine (27). In Persian medicine, Rosa damascene is considered a gentle safe laxative and even can be prescribed for children and pregnant women (19,28).…”
Section: Discussionmentioning
confidence: 99%
“…Although more studies are needed to assess the effectiveness with reasonable certainty, the most studied OEs for anxiety and depression treatment in obstetrics are those of L. angustifolia , C. aurantium var amara , and R. damascena . Among them, the R. damascena EO is too expensive to be included in clinical practice due to the very low yield: one part of OE out of 3,000 parts of flower (Akram et al, 2020). On the contrary, the EOs of C. aurantium var.…”
Section: Discussionmentioning
confidence: 99%
“…The volatile EO components, binding the specific receptors of sensorial nasal neurons that are connected to the olfactory bulbs in the limbic system, stimulate smell, emotion, and memory connected to the hypothalamus. Through this avenue, aromatherapy acts directly on the limbic system, bypassing the oral intake of EOs, thus preserving the woman and fetus from adverse reactions (Akram et al, 2020). Similarly, this path can be pursued in all those conditions that somehow involve individual emotional response, such as delivery pain and the feeling of nausea and vomit.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that the liposoluble non-polar constituents of this plant are the main responsible for most of the activities mentioned above. The pharmacological effects on the CNS are hypnotics, antidepressants, analgesics and anticonvulsants as well as in the treatment of dementia (Boskabady et al, 2011;Akram et al, 2020). Nayebi et al (2017) found promising evidences for the effectiveness and safety of Damask rose in pain relief but highlighting the need for appropriate clinical trials to verify these indications.…”
Section: Rosaceaementioning
confidence: 99%